Exploring English Learners’ Engagement and Their Roles in the Online Language Course - Fatimah Mulya Sari (Journal of English Language Teaching and Linguistics, 2020)
In technology-enhanced language learning, student engagement and roles of learners are being popular to be exposed to a better understanding of their progress on their performance of learning, and possible pitfalls in the online language classes during the study-from-home program in the times of COVID-19. This article attempts to explore the students’ perceptions of their engagement in the online learning process. It also investigates the prominent learners’ roles in the online learning environment and the possible factors affecting their engagement or participation in the online learning process. An exploratory research design was applied to this study. The subjects were a hundred and sixty-five undergraduate students from the English Literature Department and the English Education Department. The data collected were from a questionnaire that was distributed using Google Form link via WhatsApp Group, an online interview through the ZOOM meeting, and online observation through learning management systems (LMS) Moodle used by the students. Results show that most students conveyed positive responses toward their online engagement. There were also three most prominent learners’ roles identified. These roles covered active learning, problem solvers, and knowledge seeker. Besides, most students expressed that the number of compulsory task submissions, content courses, unstable internet connection, and limited internet data become the learning factors that might demotivate them to accomplish the online activities and complete the online language course. Thus, course creators or teachers should reconsider using appropriate and effective online learning activities and online learning objects to enhance the students’ active engagement in the online course.